Who wins in an energy boom? Evidence from wage rates and housing - Grant D. Jacobsen (W.E. Upjohn Institute for Employment Research, 2016)
This paper presents evidence on the distributional effects of energy extraction by examining the recent U.S. energy boom. The boom increased local wage rates in almost every major occupational category. The increase occurred regardless of whether the occupation experienced a corresponding change in employment, suggesting a more competitive labor market that benefited local workers. Local housing values and rental prices both increased, thereby benefiting landowners. For renters, the increase in prices was completely offset by a contemporaneous increase in income. The results indicate that bans on drilling have negative monetary consequences for a large share of local residents.
Keywords: J23; Q33; R31; 330; oil; natural gas; hydraulic fracturing; fracking; resource extraction; labor market effects; resource curse; Dutch disease; wage rates; housing values; rental prices